Investigation of the possible relationship between mutation at three-dimensional structural level and resistance of culex pipien's esterases to insecticides - Duong, Dam Bach; Laurent, Chiche (VNU Journal of Science: Natural Sciences and Technology; Vol 19 No 4, 2003)
Tom